(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
In the early 1840s, Friedrich Engels and Rudolph Virchow argued that the mode of social organization was a lens through which the social patterning of disease could be understood (Scambler, 2012: 131). Virchow was reluctant to attribute disease to individual behaviour, and asserted that illness belonged to the discipline of social science (de Maio, 2010: 20). In the late 20th century Richard G. Wilkinson, a British social epidemiologist and a professor at University of Nottingham, echoed Engels and Virchow, postulating that Emile Durkheim, if he remained alive, would analyse suicide based on the modern burden in developed societies (Wilkinson, 1996: 15). This article addresses the discourse on how the imbalanced distribution of class, income and social capital contributes to the poorer physical and psychosocial health conditions among socially disadvantaged cohorts, based on the arugments made by key scholars from the field of sociology and health. This article also examines the future sociological agendeas to better examine social and health inequalities, in accordance with ideas suggested by a variety of scholars, especially Graham Scambler. The article is review-based, prompting the understandings of the contemporary debates about social and health inequalities, and what roles should sociology play in such debates.